Soviet Ideology on a Platter: Food in Lithuanian and Latvian Literature - Laurušaitė, Laura (Colloquia, 2025)
The article investigates how food imagery in contemporary Lithuanian and Latvian literature re-articulates the Soviet period and its ideological imprint. Drawing on imagological and gastropoetic perspectives, the study examines three works by Lithuanian and Latvian authors: Laima Vincė’s non-fiction text Lenin’s Head on a Platter / An American Student’s Diary from the Final Years of the Soviet Union / September 1988 – August 1989 (in Lithuanian and English 2008), Nora Ikstena’s novel Soviet Milk (Mātes piens, 2015; in English 2018) and Dace Rukšāne’s novel Russian Skin (Krieva āda, 2020; reissued in 2025). These texts demonstrate how culinary motifs illuminate power relations: meat foregrounds the intrusive dictate of Russian imperial masculinity; milk, typically associated with care, acquires a bitter taste shaped by coercive worldviews; vodka reflects the regime’s levelling pressure, while wine signals fleeting moments of inner resistance. Food-related scenes also reveal Soviet social hierarchies structured by scarcity and informal access networks. Gastronomic imagery is a means that allows Baltic authors to show the impact of the Soviet era on local identities and to illuminate the possibilities of their renewal and cultural restoration with the onset of perestroika.